White dwarfs identified in LAMOST Data Release 5. Issue 2 (30th October 2021) - Guo, Jincheng; Zhao, Jingkun; Zhang, Huawei; Zhang, Jiajun; Bai, Yu; Walters, Nikolay; Yang, Yong; Liu, Jifeng
ABSTRACT: In this paper, we report white dwarfs (WD) identified in the 5 th Data Release of the Large Area Multi-Object fibre Spectroscopic Telescope ( LAMOST ), including spectral types of DA, DB, DC, DZ, and so on. There are 2625 DA spectra of 2281 DA stars, 182 DB spectra of 166 DB stars, 62 DC spectra of 58 DC stars, 36 DZ spectra of 33 DZ stars, and many other types identified, in addition to our previous paper (Data Release 2). Amongst those sources, 393 DA stars and 46 DB stars are new identifications after cross-matching with the literature. In order to select DA candidates, we use the classification result from the LAMOST pipeline, colour-colour cut method and a random forest (RF) machine learning method. For DBs, since there is no template for DB in the pipeline model, a RF machine learning method is chosen to select candidates. All the WD candidates have been visually checked individually. The parameters of effective temperature, surface gravity, mass, and cooling age have been estimated for relatively high signal-to-noise ratio DAs and DBs. The peaks of the DA and DB mass distributions are found to be around 0.62 and 0.65 M⊙, respectively. Finally, the data and method we used to select WD candidates for the second phase of LAMOST survey are also addressed in this paper.